Soil mechanics : - Powrie, William (Spon Press, 2004)
The aim of this book is to encourage students to develop an understanding of the fundamentals of soil mechanics. It builds a robust and adaptable framework of ideas to support and accommodate the more complex problems and analytical procedures that confront the practising engineer. Soil Mechanics: Concepts and Applications covers the soil mechanics and geotechnical engineering topics typically included in university courses in civil engineering and related subjects. Physical rather than mathematical arguments are used in the core sections wherever possible. The order in which the material is presented is based on the belief that students need time to assimilate new concepts, and that too many new ideas should not be introduced all at once. New features for the second edition include: an accompanying website containing the lecturers' solutions manual; new chapters on soil strength and soil behaviour separating the basic and more advanced material to aid understanding; and a new page layout making the book more accessible.